Relationship among Phosphorus Circulation Activity, Bacterial Biomass, pH, and Mineral Concentration in Agricultural Soil - Dinesh Adhikari; Tianyi Jiang; Taiki Kawagoe; Takamitsu Kai; Kenzo Kubota; Kiwako S. Araki; Motoki Kubo (Microorganisms, 2017)
Improvement of phosphorus circulation in the soil is necessary to enhance phosphorus availability to plants. Phosphorus circulation activity is an index of soil’s ability to supply soluble phosphorus from organic phosphorus in the soil solution. To understand the relationship among phosphorus circulation activity; bacterial biomass; pH; and Fe, Al, and Ca concentrations (described as mineral concentration in this paper) in agricultural soil, 232 soil samples from various agricultural fields were collected and analyzed. A weak relationship between phosphorus circulation activity and bacterial biomass was observed in all soil samples (R2 = 0.25), and this relationship became significantly stronger at near-neutral pH (6.0–7.3; R2 = 0.67). No relationship between phosphorus circulation activity and bacterial biomass was observed at acidic (pH < 6.0) or alkaline (pH > 7.3) pH. A negative correlation between Fe and Al concentrations and phosphorus circulation activity was observed at acidic pH (R2 = 0.72 and 0.73, respectively), as well as for Ca at alkaline pH (R2 = 0.64). Therefore, bacterial biomass, pH, and mineral concentration should be considered together for activation of phosphorus circulation activity in the soil. A relationship model was proposed based on the effects of bacterial biomass and mineral concentration on phosphorus circulation activity. The suitable conditions of bacterial biomass, pH, and mineral concentration for phosphorus circulation activity could be estimated from the relationship model.